Reliability of Phonemically Loaded Sentences in Spanish for Identifying Laryngeal Dystonia by Non-Spanish Speaking Speech-Language Pathologists - Eugenia Castro, María; Timmons Sund, Lauren; Zubiaur Gomar, Fermin M.; Wilson, Melissa L.; Hapner, Edie R. (My University, 2023)
Laryngeal dystonia (LD) is a focal dystonia affecting the intrinsic laryngeal muscles. Clinical diagnosis requires subjective evaluation by experienced clinicians and is primarily based on auditory-perceptual assessment. Several speech tasks are widely accepted to elicit diagnosis specific auditory-perceptual symptoms of glottal stops in adductor LD or breathy breaks in abductor LD in spoken English. With the growing Spanish speaking population in the US and lack of Spanish speech tasks to assist in identifying LD in Spanish speaking subjects, assessing the reliability of phonemically loaded sentences in Spanish for use by non-Spanish speaking providers is critical. The first aim of this study was to develop and assess the reliability of a set of Spanish language phonemically loaded sentences designed to elicit signs and symptoms of LD. The second aim was to determine the effectiveness of non-Spanish speaking speech-language pathologists (SLPs) in identifying LD in Spanish speaking subjects using these stimuli.